Answer:
(g − f) ( 3 ) = 23
Step-by-step explanation:
( g − f ) ( x ) = g ( x ) − f ( x )
= 6 x − ( 4 − x 2 )
= x 2 + 6 x − 4
to evaluate ( g - f ) ( 3 ) substitute x = 3 into ( g − f ) ( x )
( g − f ) = ( 3 ) 2 + ( 6 x 3 ) - 4 =23
Answer:
a < b < c
Step-by-step explanation:
a is -4, which is less than b, at 1, and c at 7.
If this answer is correct, please make me Brainliest!
Answer: 72 square inches
step-by-step explanation:
the equation for surface area is 2lw+2lh+2hw
breaking each of the sides down,
the length is 6 inches
the width is 2 inches
and the height is 3 inches
now substitute these into the equation
2(6)(2)+2(6)(3)+2(3)(2)
24+36+12
72 square inches
9514 1404 393
Answer:
y = -8x -15
Step-by-step explanation:
It can be useful to start with the point-slope form when you are given a point and a slope.
y -k = m(x -h) . . . . . line with slope m through point (h, k)
For the given line, this equation is ...
y +7 = -8(x +1)
y = -8x -8 -7 . . . . eliminate parentheses, subtract 7
y = -8x -15 . . . . . slope-intercept form
Answer:
![\$6](https://tex.z-dn.net/?f=%5C%246)
Step-by-step explanation:
we know that
Using proportion
![\frac{12}{4}\frac{dollars}{pounds} =\frac{x}{2}\frac{dollars}{pounds}\\ \\ x=12*2/4\\ \\x=\$6](https://tex.z-dn.net/?f=%5Cfrac%7B12%7D%7B4%7D%5Cfrac%7Bdollars%7D%7Bpounds%7D%20%3D%5Cfrac%7Bx%7D%7B2%7D%5Cfrac%7Bdollars%7D%7Bpounds%7D%5C%5C%20%5C%5C%20x%3D12%2A2%2F4%5C%5C%20%5C%5Cx%3D%5C%246)